Analisis Kemampuan Berpikir Intuisi Peserta Didik Pada Mata Pelajaran Dasar Elektronika - AT, Akrimy; Lastya, Hari Anna; sadrina, sadrina (Universitas Negeri Makassar, 2023)
Thinking is a process of mental activity experienced by someone when faced with a problem or situation that must be solved. Intuitive thinking is part of the logical aspect that develops one's ability to analyze spontaneously, quickly and precisely on a problem. In this study, the researchers aimed to determine the intuitive thinking skills of students at SMK Muhammadiyah Banda Aceh in solving basic electronics problems. Researchers used qualitative methods with descriptive type. In this research phase, the researcher used an instrument in the form of a test in the form of essay test questions. The subjects addressed in this study were students of SMK Muhammadiyah Banda Aceh, totaling 7 people including 4 people from class X and 3 people from class XI in the field of Audio Video Engineering study. The results of the study showed the intuitive thinking skills of students at SMK Muhammadiyah Banda, namely out of 7 students, 3 of them had the ability to think intuitively. The conclusion of this study is that students at SMK Muhammadiyah Banda Aceh are stated to lack the ability to think intuitively.